Tannic acid modified gelatin-based hydrogel wound dressing and preparation method thereof
Patent Information
- Application Number
- CN202211110648.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-09-13
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2042-09-13
AI Technical Summary
The prior art has problems such as weak adhesion, low mechanical strength and poor mechanical matching with the tissue in tissue trauma repair, which is difficult to meet the requirements of clinical application.
By chemically modified tannic acid and gelatin, change the spiral spiral structure of the gelatin, form a hydrogel with better liquidity and flexibility, and quickly cross -linking through the supporting effect of FeCL3 to form antibacterial and tissue stickiness Affective water gel wound dressing.
The good flexibility and self -healing performance of the hydraulic wound dressing is realized, the antibacterial performance and tissue adhesion performance is enhanced, the risk of seepage and infection is reduced, and wound healing is promoted.
Smart Images

Figure HDA0003842970550000011 
Figure HDA0003842970550000012 
Figure HDA0003842970550000021
Abstract
Description
Technical Field
[0001] The patent of the present invention belongs to the technical field of polymer materials and is a hydrogel wound dressing and a preparation method thereof, and specifically relates to a tannic acid-modified gelatin-based hydrogel wound dressing and a preparation method thereof. Background Art
[0002] Severe trauma is a major cause of death, with more than 5.8 million people dying from it worldwide each year. About 40% of traumas lead to uncontrollable bleeding or other serious consequences. Currently, in clinical tissue trauma repair, wounds are usually closed by suturing with needles and threads or stapling with a skin stapler. The advantages of suturing and stapling are that the wound is tightly closed and will not easily crack. The disadvantages are that the risk of wound infection is high, exudate and scabs form, and after sutures and skin staples are inserted into the tissue, they are prone to proliferation and keloid formation, and the sutures and staples need to be removed after a period of time.
[0003] The research and application of medical adhesives have attracted much attention, such as cyanoacrylate, fibrin glue and Focalseal. Medical adhesives are easy to use, quick, antibacterial, waterproof, non-exudative, scar-free, and have good biodegradability. They do not require secondary surgery and reduce the pain of patients. However, due to the problems of weak adhesion, low mechanical strength and poor mechanical compatibility with tissues, tissue adhesives still cannot meet the requirements of clinical applications. Summary of the invention
[0004] In order to solve the problems in the background technology, the present invention provides a tannic acid-modified gelatin-based hydrogel wound dressing and a preparation method thereof. The present invention uses tannic acid to chemically modify gelatin, changing the spatial helical structure of gelatin, making its solution more fluid at room temperature, and finally forming a more flexible hydrogel; and the introduction of phenolic hydroxyl groups on tannic acid can not only destroy bacterial cell membranes and improve the antibacterial properties of the hydrogel, but also interact covalently or non-covalently with thiol, amino and other groups on the tissue surface, thereby improving the tissue adhesion properties of the hydrogel. FeCl3 solution is used as a cross-linking agent, and FeCl3 can be used to crosslink the wound dressing. 3+ The coordination with phenolic hydroxyl groups rapidly forms a hydrogel while minimizing the damage to normal tissues.
[0005] The technical solution adopted by the present invention is:
[0006] 1. A tannic acid modified gelatin-based hydrogel wound dressing
[0007] By blowing air, part of the phenolic groups of tannic acid are oxidized to quinone groups, which then undergo Michael addition reaction with the amino groups of gelatin to obtain a hydrogel precursor solution. In the presence of FeCl3 solution, the hydrogel precursor solution will rapidly undergo sol-gel transition to form a hydrogel.
[0008] The gelatin selected was derived from pig skin.
[0009] 2. Preparation method of tannic acid modified gelatin-based hydrogel wound dressing
[0010] 1) Gelatin and tannic acid oxidized by air are dissolved in PBS solution respectively to obtain gelatin solution and tannic acid solution respectively; tannic acid solution is added dropwise to the gelatin solution to obtain an initial mixed solution, and the pH of the initial mixed solution is adjusted to 8.5 to obtain a final mixed solution; air is then blown into the final mixed solution, stirred for reaction for 3 hours, and finally dilute hydrochloric acid is added dropwise to adjust the pH of the final mixed solution to neutral to obtain a tannic acid-modified gelatin solution;
[0011] 2) dialyzing the tannic acid-modified gelatin solution in deionized water for 7 days, changing the water 3 times a day, to obtain a dialyzed tannic acid-modified gelatin solution, then freeze-drying the dialyzed tannic acid-modified gelatin solution to obtain tannic acid-modified gelatin Gel-TA-0.10, and finally dissolving the tannic acid-modified gelatin Gel-TA-0.10 in a PBS solution to obtain a hydrogel precursor solution;
[0012] 3) Mixing the hydrogel precursor solution with the FeCl3 solution to obtain a tannic acid-modified gelatin-based hydrogel wound dressing.
[0013] In the step 1), by weight, the gelatin solution contains 24 parts of gelatin and the PBS solution contains 140 parts; the tannic acid solution contains 2.4 parts of tannic acid and the PBS solution contains 20 parts.
[0014] The mass ratio of the gelatin to tannic acid is 10:1.
[0015] In the step 1), the dissolution temperature of gelatin in the PBS solution is 48° C., the reaction temperature of the final mixed solution is 48° C., and the air blowing rate is 0.075 L / min.
[0016] In the step 2), the hydrogel precursor solution contains 1.5 parts of tannic acid-modified gelatin Gel-TA-0.10 and 10 parts of PBS solution, by weight.
[0017] The cross-linking agent in step 3) is a FeCl3 solution, in which, by weight, the FeCl3 content of the FeCl3 solution is 0.04 to 0.16 parts, and the PBS solution is 5 parts.
[0018] The hydrogel wound dressing has good flexibility and self-healing properties.
[0019] The hydrogel wound dressing has antibacterial properties and tissue adhesion properties.
[0020] The tannic acid-modified gelatin-based hydrogel wound dressing of the present invention is formed by cross-linking through coordination.
[0021] The polymer network of the hydrogel wound dressing provided by the present invention includes tannic acid phenolic hydroxyl groups with strong tissue adhesion and antibacterial properties and a gelatin main chain with good biocompatibility. The phenolic hydroxyl groups can inhibit the formation of a hydration layer between the hydrogel and the tissue, and then produce covalent or non-covalent interactions with amino groups, sulfhydryl groups and other groups on the tissue surface to firmly bind. The electrostatic and synergistic effects of the phenolic hydroxyl groups can change the permeability of bacterial cell membranes and inhibit the physiological activities of bacteria. FeCl3, as a cross-linking agent, greatly reduces the harm of the hydrogel system to normal tissues. 3+ The coordination effect with the phenolic hydroxyl group enables the precursor solution to quickly form a hydrogel in situ, and the hydrogel has a certain injectability, which is convenient for delivery to the wound site.
[0022] The beneficial effects of the present invention are as follows:
[0023] 1. The tannic acid-modified gelatin-based hydrogel wound dressing provided by the present invention has a simple preparation process and low raw material price;
[0024] 2. The tannic acid-modified gelatin-based wound dressing provided by the present invention has in situ injectability, strong tissue adhesion, good biocompatibility, significant antibacterial ability and flexibility;
[0025] 3. The tannic acid-modified gelatin-based hydrogel wound dressing provided by the present invention can firmly cover the wound surface, reduce exudate, maintain a moist environment, inhibit bacterial growth, form a temporary protective layer, and promote wound healing in the dynamic physical and chemical environment of the human body. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 80% deformation compression curves of gelatin, Gel-TA-0.10 and Gel-TA-0.10-0.20FeCl3 hydrogels.
[0027] Figure 2 Rheological property images of Gel-TA-0.10-0.05FeCl3, Gel-TA-0.10-0.10FeCl3 and Gel-TA-0.10-0.20FeCl3 hydrogels at step strains of 1% to 500% (37°C, 1Hz).
[0028] Figure 3 The graph shows the tissue adhesion lap shear data of gelatin, Gel-TA-0.10-0.05FeCl3, Gel-TA-0.10-0.10FeCl3 and Gel-TA-0.10-0.20FeCl3 hydrogels.
[0029] Figure 4 These are images of the in vitro antibacterial experiments of Gel-TA-0.10-0.05FeCl3, Gel-TA-0.10-0.10FeCl3 and Gel-TA-0.10-0.20FeCl3 hydrogels against Escherichia coli. DETAILED DESCRIPTION
[0030] The present invention is described in more detail below in conjunction with specific embodiments, but the embodiments of the present invention are not limited thereto.
[0031] Embodiments of the present invention are as follows:
[0032] Example 1
[0033] 2.4 g of tannic acid was stirred in 20 mL of PBS solution at 48 ° C until completely dissolved to obtain a tannic acid solution, 24 g of gelatin was stirred in 140 mL of PBS solution at 48 ° C until completely dissolved to obtain a gelatin solution, and then 20 mL of 0.12 g / mL tannic acid solution was added dropwise thereto, and the pH value of the initial mixed solution was adjusted to 8.5 using 1 mol / L NaOH, and then the reaction was continued at 48 ° C for 3 h. The pH value of the mixture during the reaction was monitored with pH test paper every 20 min, and 1 mol / L NaOH solution was added dropwise to maintain pH = 8.5. During the entire reaction process, air was blown in at a rate of 0.075 L / min. After the reaction was completed, the pH value of the solution was adjusted to 7.4 with 1 mol / L HCl solution, and then the solution was dialyzed with deionized water for 7 days, with the water changed 3 times a day, and finally freeze-dried to obtain tannic acid modified gelatin Gel-TA-0.10. The tannic acid-modified gelatin Gel-TA-0.10 was sealed and stored in a dry place at -20°C.
[0034] The tannic acid modified gelatin Gel-TA-0.10 obtained above was prepared into 1 mL of 13 wt% hydrogel precursor solution, and then 0.5 mL of 0.05 mol / L, 0.10 mol / L, and 0.20 mol / L FeCl3 were used as cross-linking agents, respectively, and the two were mixed to prepare the corresponding hydrogels.
[0035] The results of this example are as follows Figure 1 and Figure 2 As shown, Figure 1The 80% deformation compression curves of gelatin, Gel-TA-0.10 and Gel-TA-0.10-0.20FeCl3 hydrogels. During the compression process, the stress of Gel-TA-0.10 and Gel-TA-0.10-0.20FeCl3 hydrogels increased with the increase of deformation rate, while the stress curve of gelatin dropped sharply at a deformation rate of about 70%, which means that the gelatin was damaged. Gel-TA-0.10 and Gel-TA-0.10-0.20FeCl3 hydrogels showed good flexibility and could well match the normal contraction and relaxation of tissues without being damaged.
[0036] Figure 2 These are the rheological properties images of Gel-TA-0.10-0.05FeCl3, Gel-TA-0.10-0.10FeCl3, and Gel-TA-0.10-0.20FeCl3 hydrogels. It can be seen from the figure that after four consecutive step oscillation strains from 1% to 100%, the elastic modulus of the hydrogel remains basically stable, which indicates that this series of hydrogels has excellent self-healing properties and can restore to its original state even if locally damaged by external forces.
[0037] Example 2
[0038] 2.4 g of tannic acid was stirred in 20 mL of PBS solution at 48 ° C until completely dissolved to obtain a tannic acid solution, 24 g of gelatin was stirred in 140 mL of PBS solution at 48 ° C until completely dissolved to obtain a gelatin solution, and then 20 mL of 0.12 g / mL tannic acid solution was added dropwise thereto, and the pH value of the initial mixed solution was adjusted to 8.5 using 1 mol / L NaOH, and then the reaction was continued at 48 ° C for 3 h. The pH value of the mixture during the reaction was monitored with pH test paper every 20 min, and 1 mol / L NaOH solution was added dropwise to maintain pH = 8.5. During the entire reaction process, air was blown in at a rate of 0.075 L / min. After the reaction was completed, the pH value of the solution was adjusted to 7.4 with 1 mol / L HCl solution, and then the solution was dialyzed with deionized water for 7 days, with the water changed 3 times a day, and finally freeze-dried to obtain tannic acid modified gelatin Gel-TA-0.10. The tannic acid-modified gelatin Gel-TA-0.10 was sealed and stored in a dry place at -20°C.
[0039] The tannic acid modified gelatin Gel-TA-0.10 obtained above was prepared into 1 mL of 13 wt% hydrogel precursor solution, and then 0.5 mL of 0.05 mol / L, 0.10 mol / L, and 0.20 mol / L FeCl3 were used as cross-linking agents, respectively, and the two were mixed to prepare the corresponding hydrogels.
[0040] Fresh pig skin slices (3×2cm) with fat removed 2) Soak in PBS solution for 30 min before testing. Apply 0.2 mL of 13 wt% gelatin solution on the surface of a piece of pig skin and quickly cover it with another wet pig skin piece (bonding area: 1 × 2 cm 2 ), the sample was pressed at room temperature with a pressure of 10 kPa for 10 min, and repeated at least three times. Different Gel-TA solutions were combined with different concentrations of FeCl3 solutions, and this operation was repeated to obtain pig skin adhesion samples of the corresponding hydrogels. Afterwards, the lap shear adhesion strength of the samples was tested. The test was performed using an Instron universal testing machine (5967, USA) with a crosshead speed of 2 mm / min and a 20N load cell.
[0041] In this embodiment, Figure 3 shown. Figure 3 The lap shear data of tissue adhesion of gelatin, Gel-TA-0.10-0.05FeCl3, Gel-TA-0.10-0.10FeCl3, and Gel-TA-0.10-0.20FeCl3 hydrogels show that, within a certain range, the adhesion increases with the increase of the concentration of the crosslinking agent FeCl3, which indicates that the adhesion can be improved by adjusting the concentration of the crosslinking agent FeCl3. 3+ The concentration of Gel-TA-FeCl3 hydrogel can be changed to change the tissue adhesion of the hydrogel so as to achieve strong adhesion of the hydrogel at the wound without falling off.
[0042] Example 3
[0043] 2.4 g of tannic acid was stirred in 20 mL of PBS solution at 48 ° C until completely dissolved to obtain a tannic acid solution, 24 g of gelatin was stirred in 140 mL of PBS solution at 48 ° C until completely dissolved to obtain a gelatin solution, and then 20 mL of 0.12 g / mL tannic acid solution was added dropwise thereto, and the pH value of the initial mixed solution was adjusted to 8.5 using 1 mol / L NaOH, and then the reaction was continued at 48 ° C for 3 h. The pH value of the mixture during the reaction was monitored with pH test paper every 20 min, and 1 mol / L NaOH solution was added dropwise to maintain pH = 8.5. During the entire reaction process, air was blown in at a rate of 0.075 L / min. After the reaction was completed, the pH value of the solution was adjusted to 7.4 with 1 mol / L HCl solution, and then the solution was dialyzed with deionized water for 7 days, with the water changed 3 times a day, and finally freeze-dried to obtain tannic acid modified gelatin Gel-TA-0.10. The tannic acid-modified gelatin Gel-TA-0.10 was sealed and stored in a dry place at -20°C.
[0044] The tannic acid modified gelatin Gel-TA-0.10 obtained above was prepared into 1 mL of 13 wt% hydrogel precursor solution, and then 0.5 mL of 0.05 mol / L, 0.10 mol / L, and 0.20 mol / L FeCl3 were used as cross-linking agents, respectively, and the two were mixed to prepare the corresponding hydrogels.
[0045] Take a single colony from a pre-streaked agar plate with E. coli and place it in 10.0 mL of liquid culture medium and culture it on a shaker (37°C, 5 h). Take 1.0 mL of the bacterial solution and dilute it to 1×10 6 CFU / mL, 1.0 mL of the diluted bacterial solution was coated on the top of the sterilized Gel-TA-0.10-0.05FeCl3, Gel-TA-0.10-0.10FeCl3, and Gel-TA-0.10-0.20FeCl3 cylindrical hydrogels, and co-cultured (37°C, 16h). The control group was 1.0 mL of bacterial solution added with 1.0 mL of PBS solution. Then, 100 μL of sterile PBS solution was added to each hydrogel sample, and the surviving bacteria were gently resuspended and sonicated. The sonicated bacterial solution was collected and diluted to 1×10 4 CFU / mL to determine the overall dilution multiple, and then dilute each group by the corresponding multiple. Take 100 μL of the diluted co-culture solution of each group to apply on agar plates, culture at 37°C overnight, and observe and record the total number of colonies on the plates.
[0046] The results of each embodiment are as follows Figure 4 shown. Figure 4 (a), (b), (c) and (d) are the in vitro antibacterial experiments of Gel-TA-0.10-0.05FeCl3, Gel-TA-0.10-0.10FeCl3 and Gel-TA-0.10-0.20FeCl3 hydrogels on Escherichia coli. Compared with the blank control group, Gel-TA-0.10-0.05FeCl3, Gel-TA-0.10-0.10FeCl3 and Gel-TA-0.10-0.20FeCl3 hydrogels all showed an antibacterial rate of about 100%, indicating that this series of hydrogels has excellent antibacterial ability.
Claims
1. A method for preparing a tannic acid-modified gelatin-based hydrogel wound dressing, characterized in that: The method comprises the following steps: 1) Dissolving gelatin and tannic acid in PBS solution to obtain gelatin solution and tannic acid solution respectively; Add tannic acid solution dropwise to the gelatin solution to obtain an initial mixed solution, adjust the pH of the initial mixed solution to 8.5, and obtain a final mixed solution; then, blow air into the final mixed solution, stir and react for 3 hours, and finally, add dilute hydrochloric acid dropwise to adjust the pH of the final mixed solution to neutral, and obtain a tannic acid-modified gelatin solution; 2) dialyzing the tannic acid-modified gelatin solution in deionized water for 7 days, changing the water 3 times a day, to obtain a dialyzed tannic acid-modified gelatin solution, then freeze-drying the dialyzed tannic acid-modified gelatin solution to obtain tannic acid-modified gelatin Gel-TA-0.10, and finally dissolving the tannic acid-modified gelatin Gel-TA-0.10 in a PBS solution to obtain a hydrogel precursor solution; 3) mixing the hydrogel precursor solution with the FeCl3 solution to obtain a tannic acid-modified gelatin-based hydrogel wound dressing; In the step 1), by weight, the gelatin solution contains 24 parts of gelatin and the PBS solution contains 140 parts; the tannic acid solution contains 2.4 parts of tannic acid and the PBS solution contains 20 parts; The cross-linking agent in step 3) is a FeCl3 solution, in which, by weight, the FeCl3 solution contains 0.04 to 0.16 parts of FeCl3 and the PBS solution contains 5 parts; In the step 1), the dissolution temperature of gelatin in the PBS solution is 48°C, the reaction temperature of the final mixed solution is 48°C, and the air blowing rate is 0.075 L / min; In the step 2), the hydrogel precursor solution contains 1.5 parts of tannic acid-modified gelatin Gel-TA-0.10 and 10 parts of PBS solution, by weight.
2. The method for preparing a tannic acid-modified gelatin-based hydrogel wound dressing according to claim 1, characterized in that: The mass ratio of the gelatin to tannic acid is 10:
1.
3. A tannic acid modified gelatin-based hydrogel wound dressing, characterized in that: The gelatin-based hydrogel wound dressing is prepared according to the method for preparing a tannic acid-modified gelatin-based hydrogel wound dressing according to any one of claims 1-2.
Citation Information
Patent Citations
Preparation method of tannic acid and gelatin hydrophilic coating film
CN111760469A
Compound hydrogel patch for wound skin repair and preparation method thereof
CN113304309A
Preparation method of polylactic acid food packaging film with antibacterial property and one-way moisture resistance
CN114479148A